rút y=20-x rồi thay vào quy đồng là được thôi
Đặt y = 20 - x. Ta có:
\(\frac{\left(3+x\right)}{7+y}\Leftrightarrow\frac{\left(3+x\right)}{7+\left(20-x\right)}=7\). Bỏ ngoặc ở mẫu. Ta được
\(\Leftrightarrow\frac{\left(3+x\right)}{7+20-x}\Leftrightarrow\frac{\left(3+x\right)}{27-x}=\frac{7}{1}\)
\(\Leftrightarrow\left(3+x\right).1=\left(27-x\right).7\)
\(\Leftrightarrow\left(3+x\right).7>\left(27-x\right).7\)
\(\Leftrightarrow\left(3.7\right)+x>\left(27.7\right)-x\)
\(\Leftrightarrow21+x>189-x\)
\(\Leftrightarrow x=189:21=9\)
Vì đầu bài ta đã đặt: y = 20 - x
Thế số vào, ta có: y = 20 - 9
Suy ra y = 11
\(\Rightarrow\orbr{\begin{cases}x=9\\y=11\end{cases}}\)